Effects of agricultural pollution on earthworm in the north east of Algeria - BOUJLELLE Med Amin; BENSAYEH Zaid (My University, 2024)
The increasing use of agricultural chemicals poses significant risks to non-target soil invertebrates, particularly earthworms, which play a crucial role in maintaining soil health. This study investigates the ecotoxicological effects of the fungicide Cuivroxy and lead nitrate (PbNO3) on earthworm populations in the northeastern region of Algeria. Conducted over a period of four weeks, the research evaluates weight loss and mortality rates of earthworms exposed to three different concentrations of each chemical. Soil samples and earthworm populations were collected from four distinct sites in Souk Ahras: Ain Zena, Khedara, Ouled Idris R1, and Ouled Idris R2. The physicochemical properties of the soils were analyzed to ensure comprehensive environmental assessment. Our findings reveal significant differences in the survival rates and health conditions of earthworms subjected to Cuivroxy and PbNO3, with the latter showing more pronounced toxic effects. The most alarming results were observed in the highest concentration groups, where earthworms exhibited severe weight loss and increased mortality. This research highlights the urgent need for sustainable agricultural practices and the importance of monitoring soil health to prevent long-term ecological damage. The preliminary results underscore the potential of earthworms as bioindicators for soil contamination and stress the necessity for further studies on the reproductive toxicity and long-term impacts of these pollutants. By advancing our understanding of pesticide and heavy metal toxicity, we aim to contribute to the development of environmentally friendly agricultural policies and practices that safeguard soil ecosystems for future generations. ------------------------------------------------------------------------------------------------------------------------------ يشكلالاستخدامالمتزايدللموادالكيميائيةالزراعيةمخاطركبيرةعلىالكائناتالحيةغيرالمستهدفةفيالتربة،وخاصةالديدانالأرضية،التيتلعبدوراًحاسماًفيالحفاظعلىصحةالتربة. تهدفهذهالدراسةإلىفحصالآثارالبيئيةوالتوكسيكولوجيةلمبيدالفطرياتكويفروكسيونيتراتالرصاصعلىالديدانالأرضيةفيمنطقةشمالشرقالجزائر. تمتالدراسةعلىمدارأربعةأسابيع،حيثتمتقييمفقدانالوزنومعدلاتالوفياتللديدانالأرضيةالتيتعرضتلثلاثةتراكيزمختلفةمنكلمادةكيميائية. جمعتعيناتالتربةوسكانالديدانالأرضيةمنأربعةمواقعمختلفةفيسوقأهراس: عينالزانة،الخضارة،أولاد دريس على نطاق منطقتين.تمتحليلالخصائصالفيزيائيةوالكيميائيةللتربةلضمانتقييمبيئيشامل. كشفتالنتائجتفاوتاتكبيرةفيمعدلاتالبقاءوظروفالصحةللديدانالأرضيةالمعرضةلـكويفروكسيونيتراتالرصاص،معأنالأخيرةتظهرآثاراًسامةأكثربروزاً. ملاحظةالنتائجالأكثرإثارةللقلقفيمجموعاتالتركيزالأعلى،حيثأظهرتالديدانالأرضيةفقداناًشديداًفيالوزنوزيادةفيمعدلالوفيات. تسلطهذهالدراسةالضوءعلىضرورةالتوجهنحوالممارساتالزراعيةالمستدامةوأهميةمراقبةصحةالتربةلمنعالضررالبيئيعلىالمدىالطويل. تبرزالنتائجالأوليةإمكانيةاستخدامالديدانالأرضيةكمؤشراتحيويةلتلوثالتربةوتؤكدضرورةإجراءمزيدمنالدراساتحولالسميةالتكاثريةوالتأثيراتالبيئيةعلىالمدىالطويللهذهالملوثات. منخلالتعزيزفهمناللسميةللمبيداتالحشريةوالمعادنالثقيلة،نهدفإلىالمساهمةفيتطويرسياساتوممارساتزراعيةصديقةللبيئةتحافظعلىالنظمالبيئيةللتربةللأجيالالقادمة. -------------------------------------------------------------------------------------------------------------------------------------- L'utilisation croissante des produits chimiques agricoles pose des risques significatifs pour les invertébrés du sol non ciblés, en particulier les vers de terre, qui jouent un rôle crucial dans le maintien de la santé du sol. Cette étude examine les effets écotoxicologiques du fongicide Cuivroxy et du nitrate de plomb (PbNO3) sur les populations de vers de terre dans la région nord-est de l'Algérie. Menée sur une période de quatre semaines, la recherche évalue la perte de poids et les taux de mortalité des vers de terre exposés à trois concentrations différentes de chaque produit chimique. Des échantillons de sol et des populations de vers de terre ont été prélevés sur quatre sites distincts à Souk Ahras : Ain Zena, Khdara, Ouled Idris R1 et Ouled Idris R2. Les propriétés physico-chimiques des sols ont été analysées pour garantir une évaluation environnementale complète. Nos résultats révèlent des différences significatives dans les taux de survie et les conditions de santé des vers de terre soumis à Cuivroxy et à PbNO3, ce dernier montrant des effets toxiques plus prononcés. Les résultats les plus alarmants ont été observés dans les groupes de concentration les plus élevés, où les vers de terre ont présenté une perte de poids sévère et une mortalité accrue. Cette recherche souligne le besoin urgent de pratiques agricoles durables et l'importance du suivi de la santé des sols pour prévenir les dommages écologiques à long terme. Les résultats préliminaires soulignent le potentiel des vers de terre comme bioindicateurs de la contamination des sols et soulignent la nécessité de poursuivre les études sur la toxicité reproductive et les impacts à long terme de ces polluants. En améliorant notre compréhension de la toxicité des pesticides et des métaux lourds, nous visons à contribuer au développement de politiques et de pratiques agricoles respectueuses de l'environnement qui protègent les écosystèmes du sol pour les générations futures.